Prevalence, patterns, and associated factors for substance use among university students in Maseru, Lesotho - Kamohelo, Phoofolo; Lucy, Fernandes; Kebogile, Mokwena (Intelektual Pustaka Media Utama, 2025)
Psychoactive substance use among students has implications for early substance dependence. This study aimed to determine the prevalence, patterns, and reasons for substance use among university students in Maseru, Lesotho. There were 302 students who participated in this descriptive, cross-sectional survey. Descriptive statistics summarized the findings obtained from a self-administered online questionnaire. The prevalence rate for alcohol (44.4%), dagga (6%), and cigarette smoking (6%) was statistically significantly higher among males than females (p<0.05). Alcohol was consumed to feel good by 26.1% of the participants, 38.9% smoked cigarettes to handle stress, and 22.2% used dagga because it is easily available (22.2%). This study identified a unique pattern of substance use among university students, which is limited to alcohol, cigarettes, and dagga, with the exclusion of hard drugs. Effective and comprehensive health promotion programs should be implemented in Lesotho to prevent the introduction of hard-core psychoactive substances.